Pengaruh Brand Trust Dan Electronic Word Of Mouth Terhadap Minat Beli Pada Marketplace Tokopedia Di Kota Surabaya - Ilhan Samudra Fattah; Hery Pudjoprastyono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study was conducted to determine how Brand Trust and E-WOM influence Purchase Intention among Tokopedia users in Surabaya. The focus of the study was directed at the process of how consumers' emotional and rational factors in the digital environment shape purchasing decisions, particularly through the level of trust in the brand and reviews shared by other users. In this study, a quantitative approach was used, and Structural Equation Modeling-Partial Least Square (SEM-PLS) was chosen as the analysis method. A total of 100 respondents were selected through a purposive sampling technique to collect the primary data for this study, namely Surabaya residents who were familiar with Tokopedia but had never made a transaction there. After the data were obtained, SmartPLS was used to analyze the relationship between the variables. The analysis results showed that brand trust was a positive and significant predictor of Purchase Intention, while E-WOM also proved to have a significant positive influence. These findings confirm that the combination of brand credibility and information from online reviews can encourage consumers to purchase. Overall, this study adds to the understanding of consumer behavior in the digital era and provides input for Tokopedia in its efforts to strengthen trust and brand image in the Indonesian e-commerce market